A qualitative approach to Canva as a mathematics learning medium and its implementation in undergraduate students - Riswanda, Kian Surya Seba; Rakhmawati, Intan Aulia (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2025)
The 5.0 society learning era must keep pace with technological developments to avoid monotony. Similarly, mathematics learning, including in universities, needs to adapt. Mathematics, often considered difficult and complex by undergraduate students, is expected to be easier to understand when integrated with technology. Through a qualitative approach, this study aimed to analyze the use of Canva as a medium for learning mathematics in a college environment. Canva is a web-based graphic design platform accessible to all groups. The use of Canva in mathematics education had a positive impact on undergraduate students’ engagement, creativity, and motivation. Canva offers a variety of features, including a whiteboard. This feature enables lecturers and undergraduate students to create an engaging learning atmosphere and easy-to-understand teaching materials. They could monitor the progress of discussions both individually and in groups. However, technology-based learning using Canva was not always run smoothly. An unstable internet connection could hinder the learning process with Canva, causing it to lag or even pause temporarily. Limited user knowledge and learning time also pose challenges during its implementation. These hurdles could be overcome with adequate institutional support and training. Therefore, using Canva in mathematics education could be an innovative approach that fosters digital transformation.